The development of the Mexican Familial Hypercholesterolemia (FH) National Registry. (October 2018) - Mehta, Roopa; Martagon, Alexandro J.; Galan Ramirez, Gabriela A.; Gonzalez Retana, Gustavo; Martinez-Beltran, Magdalena; Vargas Vazquez, Arsenio; Vazquez-Cardenas, Alejandra; Aguilar-Salinas, Carlos A.
Abstract: Background and aims: In Mexico, familial hypercholesterolemia (FH) is, as in other parts of the world, largely underdiagnosed and undertreated, and represents a significant burden to the healthcare system. However, there is not enough information to design public policies against the disease. Genetic studies have shown that LDLR mutations are the most common cause, but in a large percentage of the cases, no mutation has been identified in the FH genes. Methods: In accordance with the procedures of the European Atherosclerosis Society (EAS) FH registries network, the Mexican FH registry (www.fhmexico.org.mx ) was launched in December 2017 to address the gaps in knowledge regarding this disease. Reference centres and the main nationwide public health providers have been invited to participate. Results: To date, 142 cases have been registered. The mean age at diagnosis of probands is 36.42 ± 19.9 years (adults and children). Tendon xanthomas or premature corneal arcus were present in 40% and 17.6%, respectively. Molecular analysis was present in 70%, with over 95% of alterations located on the LDL receptor gene. The median untreated LDL-C is 6.5 (5.6–8.4) mmol/l and the median on treatment LDL-C level is 4.3 ± 1.7 mmol/l. Conclusions: The Mexican FH registry aims to obtain real world information regarding the management of patients in this country. By participating in this global call to action, we hope to improve both short and long term outcomes for all FH patients in Mexico. Highlights: In México, familial hypercholesterolemia (FH) is largely underdiagnosed and undertreated. The Mexican FH registry (www.fhmexico.org.mx ) was launched in December 2017 to address the gaps in knowledge regarding this disease. The Mexican FH registry (www.fhmexico.org.mx ) aims to obtain real world information regarding the management of patients in this country.